2012
DOI: 10.1055/s-0032-1331021
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Temporal Bone Resection in Advanced Cutaneous Squamous Cell Carcinoma: Report of 35 Patients

Abstract: Objective?To evaluate lateral temporal bone resection (LTBR) in the management of advanced cutaneous squamous cell carcinoma (SCC) with temporal bone invasion and patterns of failure. Methods?This is a retrospective study of 35 patients undergoing lateral temporal bone resection for advanced cutaneous SCC at a tertiary care center between 1995 and 2006. Results?The Pittsburgh tumor stage was T4 in 18 patients (51%), T3 in 5 (14%), T2 in 9 (26%), and T1 in 3 (9%). Clear margins were reported in 22 (63%) patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Ensuring that the margin is tumor-free after surgical resection is important. Essig et al [ 15 ] reported a DFS rate of 81% at 2 years in patients with clear margins, in contrast to a DFS rate of 45% in patients with positive margins. Moody et al [ 1 ] also reported that positive histological margins were associated with reduced survival at 2 years (32%) compared to that of patients with clear margins (75%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensuring that the margin is tumor-free after surgical resection is important. Essig et al [ 15 ] reported a DFS rate of 81% at 2 years in patients with clear margins, in contrast to a DFS rate of 45% in patients with positive margins. Moody et al [ 1 ] also reported that positive histological margins were associated with reduced survival at 2 years (32%) compared to that of patients with clear margins (75%) [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The survival rates of patients with SCCs of the EAC who undergo surgery at early stages are reportedly favorable, highlighting the importance of clinical suspicion and early diagnosis. The results of our study have been summarized along with the results of contemporary series in Table 4 [ 1 , 3 , 4 , 6 - 10 , 12 , 14 , 15 , 23 - 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In general, postoperative RT has been performed after radical surgery such as STBR or total temporal bone resection (TTBR) for stage T4 EAC cancer. In previous studies that analyzed the prognosis of T3 and T4 stages of TB SCC, a 5‐year DSS was 45%–65% 6,24,25 . The 2‐year OS was 50%–64% at T3 stage and 7%–49% at T4 stage 1,16,26,27 .…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies that analyzed the prognosis of T3 and T4 stages of TB SCC, a 5-year DSS was 45%-65%. 6,24,25 The 2-year OS was 50%-64% at T3 stage and 7%-49% at T4…”
Section: Discussionmentioning
confidence: 99%
“…This approach has shown improved locoregional control in cases of locally advanced parotid and cutaneous malignancies. [942][943][944][945]…”
Section: Advanced Skin and Parotid Gland Malignancymentioning
confidence: 99%